Reversal Agents for the Direct Factor Xa Inhibitors: Biochemical Mechanisms of Current and Newly Emerging Therapies - Schreuder, Mark; Reitsma, Pieter H.; Bos, Mettine H. A. (Seminars in Thrombosis and Hemostasis, 2020)
The direct oral anticoagulants targeting coagulation factor Xa or thrombin are widely used as alternatives to vitamin K antagonists in the management of venous thromboembolism and nonvalvular atrial fibrillation. In case of bleeding or emergency surgery, reversal agents are helpful to counteract the anticoagulant therapy and restore hemostasis. While idarucizumab has been established as an antidote for the direct thrombin inhibitor dabigatran, reversal strategies for the direct factor Xa inhibitors have been a focal point in clinical care over the past years. In the absence of specific reversal agents, the off-label use of (activated) prothrombin complex concentrate and recombinant factor VIIa have been suggested as effective treatment options during inhibitor-induced bleeding complications. Meanwhile, several specific reversal agents have been developed. In this review, an overview of the current state of nonspecific and specific reversal agents for the direct factor Xa inhibitors is provided, focusing on the biochemistry and mechanism of action and the preclinical assessment of newly emerging therapies.
Keywords: factor Xa inhibitors; hemorrhage; anticoagulants; antidotes